Evaluation the Hydraulic Performance of Drip Irrigation System with Multi Cases - Mohammed A. Almajeed A. Alabas (Global Journals of Research in Engineering, 2013)
Drip Irrigation Method is the best method that has been used in the world among the other irrigation methods because of its good and high uniformity. This method distributes water to the field using the pipe network and transforms it from the pipe network to the plant by emitters. In spite of the advantages of drip Irrigation method, the traditional network in drip irrigation method has many problems. The main problem is the drop in pressures and discharges distribution in the network resulting from the amount of pressure losses between the head of the lateral as compared with that in the end of the lateral. This drop affects the discharge distribution of emitters and uniformity. The research studies the improvement of emission uniformity of emitters by using new system layouts instead of the traditional system. The first proposed system layout concluded to improve the hydraulic performance by improving the pressure of distribution in the system by connecting the ends of the laterals together in the subunit. For further improvement, a carrier (close pipe convey the water) near the source to the lateral ends has been added to the looped network to represent the second proposed system (looped with carrier network) traditional network in drip irrigation method has many problems. The main problem is the drop in pressures and discharges distribution in the network resulting from the amount of pressure losses between the head of the lateral as compared with that in the end of the lateral. This drop affects the discharge distribution of emitters and uniformity. The research studies the improvement of emission uniformity of emitters by using new system layouts instead of the traditional system. The first proposed system layout concluded to improve the hydraulic performance by improving the pressure of distribution in the system by connecting the ends of the laterals together in the subunit. For further improvement, a carrier (close pipe convey the water) near the source to